Clinical, pharmacology and in vivo studies of QingDai (indigo naturalis) promotes mucosal healing and symptom improvement in ulcerative colitis by regulating the AHR-Th17/Treg pathway - Sizhen Gu; Yan Xue; Xiaowen Liu; Yini Tang; Dong Wang; Dongmei Wu; Mingrong Yao; Zehua Xia; Sen Yang; Gan Cai; Shigui Xue; Danbo Dou (Journal of Inflammation)
Abstract Qingdai (QD), derived from various plant sources, is commonly used in traditional Chinese medicine for ulcerative colitis (UC) treatment. However, the clinical efficacy and mechanisms of orally administered QD remain unclear. This study aims to evaluate QD’s efficacy in UC treatment and uncover its active components and mechanisms. A randomized controlled trial compared QD to Adisa, followed by UPLC-Q-TOF/MS and network pharmacology analyses to identify QD’s core components and targets. In vivo experiments on a UC mouse model explored QD’s impact on the AHR-Th17/Treg pathway using PCR, WB, ELISA, and flow cytometry. Results showed QD’s efficacy in UC treatment, with mucosal healing and remission comparable to Adisa. UPLC-Q-TOF/MS identified 16 core components in mouse colon tissue, with network pharmacology revealing 67 targets, potentially involving the IL-17 signaling pathway and Th17 cell differentiation. QD and its components up-regulated AHR, CYP1A1, and Foxp3, while down-regulating RORγt. Additionally, QD modulated pro-inflammatory (IL-6, IL-17 A) and anti-inflammatory (IL-10, TGF-β1) factors, and Treg/Th17 cell ratios in LPMC. Oral QD administration effectively promoted mucosal healing and improved UC symptoms, potentially through AHR-Th17/Treg pathway regulation.